“Superior Vena Cava Syndrome: case report” - Costa, Maria Fernanda Fernandes Duarte (2018)
Superior vena cava syndrome (SVCS) occurs when there is obstruction of the superior vena cava. The most common causes of SVCS are malignancies and small cell lung cancer is its second major etiology. The authors describe a case of superior vena cava syndrome caused by small cell lung cancer (oat cell type) in a smoker complaining of cough, dyspnea, facial edema and plethora. Relief of obstructive symptoms represents the initial treatment. Radiation therapy should not be indicated empirically, since it requires the histological diagnosis of malignancy.